Perubahan Iklim dalam Perspektif Regulasi dan Kebijakan Lingkungan di Indonesia - Setiawan, Tomi; Mughits, Muhammad Hammam; Halim, Hilman Abdul (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Indonesia is currently faced with significant environmental problems stemming from industrial activities, deforestation, and peatland burning, which substantially increase greenhouse gas emissions and accelerate environmental degradation. This paper aims to analyze an extensive review of the literature related to regulations and policies on climate change, within international and national legal frameworks. The paper also further explores significant advances in environmental law related to climate change, covering issues such as human rights, climate litigation, and the obligations of sovereign states and corporate entities. The method used in this research is a qualitative research method based on the Integrated Literature Review (ILR) approach, which focuses on the intrinsic logic and coherence of legal documents in general. The results of the analysis show that a legal perspective is increasingly important in addressing climate change, given that laws, treaties and regulations can take a central role in mitigating and adapting to the impacts of climate change. Specifically, climate change law encompasses a wide array of legal instruments and mechanisms at the international, national, and local levels, all of which aim to reduce greenhouse gas (GHG) emissions, increase climate resilience, and promote climate justice. In conclusion, this study, climate change has emerged as an urgent global challenge that requires legal and regulatory interventions at various levels. In addition, the legal perspective plays an important role in explaining the roles and responsibilities of the state, individuals, communities, and the private sector in the field of climate change mitigation and adaptation. As a recommendation to strengthen climate policy in Indonesia, it is imperative to advocate for legal reforms that are responsive to international advancements and improve the capacity of the judiciary in handling environmental litigation, thereby facilitating effective implementation of climate change law.